When Cooperation Meets Animation: How Audiovisual-Driven Learning Ecosystems Shape Student Cognitive Engagement - Ahmad Hariyadi; Wawan Shokib Rondli; Fatikhatun Najikhah; Dumiyati Dumiyati; Siti Aniqoh Shofwani (Assyfa Learning Journal, 2026)
Background: In the Society 5.0 era, higher education institutions face significant challenges in overcoming student passivity and cultivating critical 21st-century skills within foundational courses. Objective: This study aims to investigate the implementation of cooperative learning models driven by audiovisual media in shaping student cognitive engagement and social interaction within university learning ecosystems. Method: Adopting a qualitative case study approach, data were gathered through semi-structured interviews, intensive class observations, and focus group discussions involving lecturers and students at Muria Kudus University and PGRI Ronggolawe University, with qualitative analysis executed via the Miles and Huberman framework. Results: The findings demonstrate that integrating audiovisual-driven learning ecosystems—incorporating interactive animations and instructional videos—creates a dynamic, student-centered environment that successfully bridges abstract theoretical concepts with concrete examples. Structured cooperative groups fostered robust individual and group accountability, which substantially enhanced peer communication, high-order critical thinking, and collective problem-solving capabilities among students. Conclusion: The study concludes that the synergy where cooperation meets animation provides a highly effective instructional architecture that optimizes academic learning outcomes, mitigates passivity, and develops vital professional soft skills, positioning it as a robust pedagogical strategy for modern instructional science.